1993
DOI: 10.3758/bf03205276
|View full text |Cite
|
Sign up to set email alerts
|

Visual influences on auditory pluck and bow judgments

Abstract: In the McGurk effect, visual information specifying a speaker's articulatory movements can influence auditory judgments of speech. In the present study, we attempted to find an analogue of the McGurk effect by using nonspeech stimuli-the discrepant audiovisual tokens of plucks and bows on a cello. The results of an initial experiment revealed that subjects' auditory judgments were influenced significantly by the visual pluck and bow stimuli. However, a second experiment in which speech syllables were used demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 39 publications
6
76
0
1
Order By: Relevance
“…To ensure that they were attending to the visual information, as in previous studies they were also required to rate the degree to which the auditory and visual components of the stimulus agreed, using a second on-screen slider with endpoints labeled "Low agreement" and "High agreement." Rosenblum and colleagues (Rosenblum & Fowler, 1991;Saldaña & Rosenblum, 1993) have shown that this secondary task regarding audio-visual through each other. The presentation of a tone at the moment of overlap increased the likelihood that the event was perceived as a bounce.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure that they were attending to the visual information, as in previous studies they were also required to rate the degree to which the auditory and visual components of the stimulus agreed, using a second on-screen slider with endpoints labeled "Low agreement" and "High agreement." Rosenblum and colleagues (Rosenblum & Fowler, 1991;Saldaña & Rosenblum, 1993) have shown that this secondary task regarding audio-visual through each other. The presentation of a tone at the moment of overlap increased the likelihood that the event was perceived as a bounce.…”
Section: Methodsmentioning
confidence: 99%
“…2006), and cello sounds (Saldana and Rosenblum 1993). Moreover, click‐vowel Zulu syllables that are perceived by American English listeners as non‐speech (Best et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that this approach does not interfere with the primary task (Rosenblum & Fowler, 1991;Saldaña & Rosenblum, 1993). Because the purpose of these ratings was only to draw the participants' attention to the visual component of the stimulus, we did not analyze them.…”
Section: Participants and Proceduresmentioning
confidence: 99%